(untitled) (Eurasian Research Bulletin, 2023)
The profit tax is a significant source of revenue for the state budget in Uzbekistan. As such, it is essential to ensure effective tax administration and compliance. However, there are several challenges in the tax administration of profit tax in Uzbekistan, including complex tax legislation, inadequate taxpayer education, insufficient use of modern technology, and corruption. This paper aims to review the literature on ways to improve the tax administration of profit tax in Uzbekistan. The review covers studies published between 2010 and 2021. The study finds that improving the tax administration of profit tax in Uzbekistan requires a comprehensive approach that includes simplification of tax legislation, taxpayer education and awareness, and modernization of tax administration systems. Additionally, it is necessary to increase the capacity of tax authorities to identify and prosecute cases of tax evasion and corruption. The review of literature provides insights into the experiences of other countries, such as the United States, Russia, and South Korea, in improving tax administration. The findings of this study have significant implications for policymakers and tax authorities in Uzbekistan in designing and implementing effective tax administration strategies for profit tax